Sanitary ceramic adhesive slurry and preparation method thereof, and split toilet
By mixing the composition of the bonding slurry and adding specific auxiliary materials, the problems of unstable solid content and low bond strength of the ceramic bonding slurry are solved, and the ceramic bonding effect with high strength, low shrinkage and good stability are achieved.
Patent Information
- Application Number
- CN202410662171.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-27
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-05-27
AI Technical Summary
The solid content of the existing ceramic bonding slurry is unstable and the drying shrinkage is inconsistent, resulting in low bonding strength, easy cracking, and poor stability, which affects the bonding quality of large-scale ceramic products such as toilets.
By mixing the relative content of mud and mud dry powder or wet powder, the solid content of the bonding slurry is increased, wollastonite, white glaze and sodium carboxymethylcellulose are added, the chemical composition and stirring process of the bonding slurry are improved, and the bonding strength and stability are improved.
The bonding strength of dry blank and porcelain bonding strength are improved, the drying shrinkage rate is reduced, the water retention and stability of the bonding slurry is enhanced, the stress cracks and thermal shock damage of the product are reduced, and the bonding efficiency and product qualification rate are improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic manufacturing, in particular to a sanitary ceramic adhesive slurry and a preparation method thereof, and a split toilet. Background Art
[0002] For the sanitary ceramics industry, the production of large ceramic products such as toilets has changed from traditional one-piece molding to high-pressure modular splicing molding, which has the advantages of improved work efficiency and simplified structure. With the transition from one-piece molding to high-pressure modular splicing molding, higher requirements are put forward for sanitary ceramic production. It is particularly important to realize high-pressure rapid modular splicing production of large products such as toilets. A high-performance, high-quality modular adhesive slurry can improve production efficiency and product quality, thereby saving resources.
[0003] In the prior art, the adhesive slurry is basically made in the form of mud + mud blocks. The adhesive slurry made in this way is more convenient, but the solid content of the mud blocks is unstable, the water content is high, the number of mud blocks required for preparation is large, the stirring cycle is long, and the stirring uniformity is poor. The solid content of ordinary adhesive slurry is generally 70%-73%, while the solid content of the workpiece to be bonded is generally 79%-85%. The solid content of the adhesive slurry is very different from that of the workpiece to be bonded, and the drying shrinkage rate is inconsistent. It is easy to crack when drying, resulting in low dry blank bonding strength and porcelain bonding strength. In addition, ordinary adhesive slurry also has the problems of easy air drying and poor stability, resulting in the gradual hardening of the adhesive slurry when the toilet is bonded for more than a certain period of time, and the viscosity of the adhesive slurry becomes lower, reducing the bonding pass rate. In the face of large adhesive products such as toilets, the low bonding strength cannot withstand the stress and tension from different directions during the later cooling process, causing the product to crack. For large toilets such as toilets with complex bonding structures, higher dry blank bonding strength and porcelain bonding strength are required, and the existing bonding slurry technology cannot meet the requirements.
[0004] In the process of preparing bonding slurry, ordinary mixers generally adopt a multi-blade rotating fixed stirring method. During the stirring process, the contact area between the blades and the slurry is large in the multi-blade rotating stirring. When a certain vortex is formed, the air is introduced into the bonding slurry through the blades along the stirring shaft. When the bonding slurry reaches a certain consistency, the air introduction speed is greater than the discharge rate, and the air continues to remain in the bonding slurry. The bonding slurry produced in this way has many pores, thereby forming more bubbles, which makes it easy for gaps to appear on the bonding surface, resulting in pinholes or glaze shrinkage on the glaze surface at the bonding position of the product.
[0005] Therefore, it is necessary to develop adhesive slurry with good bonding properties and improve the preparation method of adhesive slurry. Summary of the invention
[0006] The present invention aims to solve at least one of the above-mentioned technical problems in the related art to a certain extent. To this end, the present invention proposes a sanitary ceramic adhesive slurry, which can improve the dry blank bonding strength and the ceramic bonding strength, the drying shrinkage rate is close to the bonding mud blank, the adhesive slurry has good water retention performance, good stability, no stress cracking of large-piece bonding products, good thermal shock resistance, can realize the bonding of products of any shape, has good bonding efficiency, and has few defects in the bonding position of the product.
[0007] The invention also provides a method for preparing the sanitary ceramic adhesive slurry.
[0008] The present invention also provides a split toilet bowl whose preparation raw materials contain the sanitary ceramic adhesive slurry.
[0009] According to one aspect of the present invention, a sanitary ceramic adhesive slurry is proposed, comprising the following components: a main material, wollastonite, white glaze, and sodium carboxymethyl cellulose. The main material comprises mud and solid material, and the solid material is at least one of mud blank dry powder or wet blank.
[0010] It should be noted that the mud is the mud used to produce bonding products, the white glaze is the sanitary ceramic white glaze, the chemical composition of the main material after dehydration is the same as the chemical composition of the mud to be bonded after dehydration, and the chemical composition of the mud after dehydration is the same as the chemical composition of the dry mud powder and the wet mud.
[0011] In some embodiments of the present invention, the solid content of the sanitary ceramic adhesive slurry is 75%-80%, and the solid content is controlled by the relative content of the mud and the solid material.
[0012] In some embodiments of the present invention, the components are calculated in the following parts by weight: 90-110 parts of the main material, 1-3 parts of wollastonite, 2-5 parts of white glaze, and 0.03-0.08 parts of sodium carboxymethyl cellulose.
[0013] In some embodiments of the present invention, when the solid material is dry clay powder, the mass ratio of the mud to the dry clay powder is (7-8): (2-3), and the solid content of the mud is 68%-73%. Dry clay powder contains almost no water, which can effectively achieve the purpose of increasing the solid content to a higher level, and has good dispersibility, is easy to stir evenly, and has a short stirring cycle. Wet clay is also an optional solution. The solid content of wet clay is generally 78%-80%. The relative amounts of mud and wet clay can be adjusted according to the moisture content of the wet clay and the target solid content of the sanitary ceramic adhesive slurry.
[0014] In some embodiments of the present invention, the chemical composition of the sanitary ceramic adhesive slurry includes, by mass percentage: Fe2O3: 0-1.2%, MgO: 0.2%-0.6%, CaO: 1%-3.5%, TiO2: 0-0.5%, Al2O3: 20%-24%, SiO2: 60%-72%, K2O: 3%-4.5%, Na2O: 0.5%-1.5%, ZrO2: 0.05%-0.52%.
[0015] In some embodiments of the present invention, the chemical composition of the white glaze includes, by mass percentage: Fe2O3: 0-1.2%, MgO: 1%-2%, CaO: 10%-14%, TiO2: 0-0.5%, Al2O3: 8%-12%, SiO2: 60%-65%, K2O: 0-2%, Na2O: 2%-4%, and ZrO2: 5%-12%.
[0016] In some embodiments of the present invention, the chemical composition of the mud, measured by mass percentage, includes: Fe2O3: 0-1.2%, MgO: 0.2%-0.6%, CaO: 0-1%, TiO2: 0-0.5%, Al2O3: 20%-24%, SiO2: 60%-72%, K2O: 3%-4.5%, Na2O: 0.5%-1.5%, ZrO2: 0-0.5%.
[0017] In some embodiments of the present invention, the chemical composition of the wollastonite includes, by mass percentage: CaO: 40%-48%, SiO2: 52%-60%.
[0018] In some embodiments of the present invention, the sanitary ceramic adhesive slurry includes the following properties: water film disappearance time is 20-35 min, workpiece drying strength is 3-3.5 MPa, and workpiece firing strength is 60-80 MPa.
[0019] According to another aspect of the present invention, a method for preparing the sanitary ceramic adhesive slurry is provided, comprising the following steps:
[0020] S1: Put the slurry into a dough mixer, add wollastonite and white glaze and stir, wherein the dough mixer has a dough hook;
[0021] S2: adding sodium carboxymethyl cellulose to the material stirred in step S1 and stirring;
[0022] S3: adding solid material to the material stirred in step S2 and stirring to obtain the sanitary ceramic adhesive slurry.
[0023] In some embodiments of the present invention, the stirring speed is 60-100 r / min.
[0024] According to another aspect of the present invention, a two-piece toilet is provided, wherein the raw materials for preparing the two-piece toilet include the sanitary ceramic adhesive slurry.
[0025] According to the embodiments of the present invention, there are at least the following beneficial effects:
[0026] 1. The present invention improves the bonding strength of the dry blank by reducing the drying shrinkage rate of the adhesive slurry: the solid content of the mud blank to be bonded of the sanitary ceramics is 79%-85%. The solid content of the adhesive slurry is improved by adjusting the relative content of the mud and the mud blank dry blank powder or wet blank, so that the solid content of the adhesive slurry is close to the solid content of the mud blank to be bonded, and the drying shrinkage rate of the adhesive slurry is ensured to be close to the drying shrinkage rate of the mud blank. Increasing the solid content reduces the moisture content of the adhesive slurry and increases the density of the adhesive slurry, further improving the bonding strength of the dry blank. During the production and stirring process of the adhesive slurry, sodium carboxymethyl cellulose is added, and the water-fixing ability of the long-chain molecules in the sodium carboxymethyl cellulose is utilized to increase the water retention capacity and stability of the mud. In addition, sodium carboxymethyl cellulose is a chain structure, and mud particles are attached to it, which plays a role in enhancing the bonding strength of the adhesive slurry.
[0027] 2. The firing strength of the product is determined by the bonding strength and the strength of the bonding slurry itself. The present invention improves the bonding strength and the strength of the bonding slurry itself by the following means: by adding white glaze and wollastonite to the bonding slurry, the amount of high-temperature liquid phase of the bonding slurry is increased, and a connected liquid phase is formed between the mud particles during the sintering process, which promotes the bonding of solid phase particles and thus improves the ceramic bonding strength. By adding sanitary ceramic white glaze with a thermal expansion coefficient close to that of the green body, while ensuring the amount of liquid phase, the number of microcracks caused by the mismatch of thermal expansion coefficients is reduced, and the strength of the bonding slurry itself is improved.
[0028] 3. Use the "pinning effect" of wollastonite to improve the bonding strength of the porcelain and enhance the thermal shock resistance: Wollastonite is a triclinic crystal system with fine plate-like crystals and radial or fibrous aggregates. When wollastonite is directly added to the bonding slurry, the radial or fibrous aggregates melt at high temperatures to form a "pinning effect". When the bonding surface is subjected to force, the radial or fibrous melts act as a barrier during the expansion of microcracks, extending the expansion and convergence distance of the microcracks, thereby improving the bonding strength of the porcelain and the thermal shock resistance of the bonding surface.
[0029] 4. The present invention introduces a new stirring process and uses the dough hook of a dough mixer for stirring. The dough hook performs periodic reciprocating motion in a plane. Under the same stirring effect, the surface area of the dough hook is small, the air entrapped is less, and the produced adhesive slurry has fewer pores, which effectively reduces the bubbles in the adhesive slurry, improves the uniformity of the adhesive slurry, reduces defects in the bonding position of the product, improves the qualified rate of the product, and shortens the aging time.
[0030] 5. The present invention determines the order of adding materials according to the characteristics of each raw material of the adhesive slurry: sodium carboxymethyl cellulose will agglomerate when absorbing water. If sodium carboxymethyl cellulose is added first, it will take a long time for the later added wollastonite and white glaze to be evenly dispersed or adhere to the inner wall of the stirring container. Therefore, wollastonite and white glaze are added first to allow the two raw materials to be fully stirred to prevent agglomeration, improve the uniformity of the adhesive slurry components, reduce stirring time, and improve production efficiency.
[0031] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION
[0032] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0033] The following examples and comparative examples are provided according to the formula of sanitary ceramic adhesive slurry.
[0034] Table 1 Composition of sanitary ceramic adhesive slurry examples and comparative examples
[0035]
[0036] The chemical compositions of the raw materials used in Table 1 are shown in Table 2.
[0037] Table 2 Chemical composition of each raw material
[0038]
[0039] Preparation method of sanitary ceramic adhesive slurry:
[0040] S1: preparing a uniform semi-finished adhesive slurry: putting the slurry into a dough mixer with a dough hook, adding wollastonite and sanitary ceramic white glaze, and stirring with the dough hook to obtain a semi-finished adhesive slurry;
[0041] S2: Add sodium carboxymethyl cellulose to the uniform semi-finished adhesive slurry and stir thoroughly;
[0042] S3: Add the dry clay powder to the material stirred in step S2, stir well and evenly to obtain a finished sanitary ceramic adhesive slurry; the stirring speed of steps S1-S3 is 70r / min.
[0043] Table 3 Chemical composition of finished sanitary ceramic adhesive slurry of Examples 1-5
[0044]
[0045] Test example
[0046] The various properties of the sanitary ceramic adhesive slurry of each embodiment and comparative example were tested by the following method, and the results are shown in Table 4.
[0047] 1. Disappearance time of water film: At a temperature of 25°C and a humidity of 65%, the same volume of adhesive slurry is evenly covered on the surface of the workpiece, and the disappearance time of the hydrogel film under the light is recorded.
[0048] 2. Dry strength of bonded workpieces: prepare workpiece slurry, inject it into the strength test mold for slurry absorption and forming. After the slurry absorption is completed, take out 6 strength test strips, cut the strength test strips in the middle, use bonding slurry to bond the workpiece according to the bonding process, dry it after bonding, and after drying, scrape the uneven positions to make them smooth, and then use the flexural tester to test the dry strength, and take the average value of the 6 bonding test strips as the workpiece bonding dry strength value.
[0049] 3. Firing strength of bonded workpieces: prepare workpiece slurry, inject it into the strength test mold for slurry absorption and forming. After the slurry absorption is completed, take out 6 strength test strips, cut the strength test strips in the middle, use bonding slurry to bond the workpiece according to the bonding process, dry it after bonding, and after drying, scrape the uneven position to make it flat, place it in the production tunnel kiln and fire it according to the production process conditions. After firing, use a flexural tester to test the firing strength, and take the average value of the 6 bonding test strips after firing as the workpiece bonding firing strength.
[0050] 4. Thermal shock resistance test: prepare the workpiece slurry, inject it into the mold with a length * width: 12 * 12cm and a thickness of 12mm to absorb the slurry and form a total of 5 pieces. After the slurry absorption is completed, take out the test block, cut the test block from the middle, use the adhesive slurry to bond the workpiece according to the bonding process, dry it after bonding, and after drying, scrape the uneven position flat, place it in the production tunnel kiln and fire it according to the production process conditions. After firing, place it in a 145℃ oven for 1h, quickly put it in 5℃ ice water, soak it in ink for 5min after 10min, check whether there is crack or cracking, if there is no crack, repeat it in the 145℃ oven to heat up, and perform a cycle test, record the number of cycles of each bonding test block until cracking, and take the average number of cycles of 5 test blocks as the thermal shock resistance value. This value represents the level of thermal shock resistance. The higher this value, the better the thermal shock resistance.
[0051] Table 4 Performance test of sanitary ceramic adhesive slurry
[0052]
[0053] As can be seen from Table 1 and Table 4, Comparative Example 1 uses pure mud as ordinary bonding slurry without adding any auxiliary ingredients. Its solid content is lower than that of each embodiment, and the water film disappears quickly, indicating that it is easy to air dry, has poor stability, and the workpiece drying strength and firing strength are both low. Comparative Example 2 omits wollastonite on the basis of Example 1, and the workpiece firing strength and thermal shock resistance are significantly reduced, indicating that wollastonite can utilize its "pinning effect" to improve the porcelain bonding strength and thermal shock resistance. Comparative Example 3 omits sodium carboxymethyl cellulose on the basis of Example 1, and the water film disappears significantly. The time, indicating that the water retention capacity is reduced, and because sodium carboxymethyl cellulose itself has the effect of improving strength, the comprehensive influence leads to a significant reduction in the workpiece drying strength and workpiece firing strength of Comparative Example 3. It should be noted that there are many types of thickeners, most of which use ion exchange or have a strong water absorption capacity to achieve the purpose of thickening, while sodium carboxymethyl cellulose has both water retention capacity and strength improvement in the present invention. Comparative Example 4 omits the sanitary ceramic white glaze on the basis of Example 1, and the drying strength and firing strength of the workpiece are reduced. The solid content of Comparative Example 4 is slightly higher than that of Example 1. This is because the solid content of the sanitary ceramic white glaze is between 62.6% and 67%. Therefore, the addition of sanitary ceramic white glaze in Example 1 will cause the solid content to be slightly reduced.
[0054] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A sanitary ceramic adhesive slurry, characterized in that: The invention comprises the following components: a main material, wollastonite, white glaze and sodium carboxymethyl cellulose, wherein the main material comprises mud and solid material, and the solid material is at least one of mud blank dry powder or wet blank; each component is calculated by the following weight parts: 90-110 parts of the main material, 1-3 parts of wollastonite, 2-5 parts of the white glaze and 0.03-0.08 parts of sodium carboxymethyl cellulose; the solid content of the sanitary ceramic adhesive slurry is 75%-80%, and the solid content is controlled by the relative content of the mud and the solid material.
2. The sanitary ceramic adhesive slurry according to claim 1, characterized in that: When the solid material is dry clay powder, the mass ratio of the mud to the dry clay powder is (7-8): (2-3), and the solid content of the mud is 68%-73%.
3. The sanitary ceramic adhesive slurry according to claim 1, characterized in that: Measured by mass percentage, the chemical composition of the sanitary ceramic adhesive slurry includes: Fe2O3: 0-1.2%, MgO: 0.2%-0.6%, CaO: 1%-3.5%, TiO2: 0-0.5%, Al2O3: 20%-24%, SiO2: 60%-72%, K2O: 3%-4.5%, Na2O: 0.5%-1.5%, ZrO2: 0.05%-0.52%.
4. The sanitary ceramic adhesive slurry according to claim 1, characterized in that: Measured by mass percentage, the chemical composition of the white glaze includes: Fe2O3: 0-1.2%, MgO: 1%-2%, CaO: 10%-14%, TiO2: 0-0.5%, Al2O3: 8%-12%, SiO2: 60%-65%, K2O: 0-2%, Na2O: 2%-4%, and ZrO2: 5%-12%.
5. The sanitary ceramic adhesive slurry according to claim 1, characterized in that: The chemical composition of the mud includes, by mass percentage: Fe2O3: 0-1.2%, MgO: 0.2%-0.6%, CaO: 0-1%, TiO2: 0-0.5%, Al2O3: 20%-24%, SiO2: 60%-72%, K2O: 3%-4.5%, Na2O: 0.5%-1.5%, ZrO2: 0-0.5%.
6. The sanitary ceramic adhesive slurry according to claim 1, characterized in that: Calculated by mass percentage, the chemical composition of the wollastonite includes: CaO: 40%-48%, SiO2: 52%-60%.
7. The method for preparing the sanitary ceramic adhesive slurry according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: Put the slurry into a dough mixer, add wollastonite and white glaze and stir, wherein the dough mixer has a dough hook; S2: adding sodium carboxymethyl cellulose to the material stirred in step S1 and stirring; S3: adding solid material to the material stirred in step S2 and stirring to obtain the sanitary ceramic adhesive slurry.
8. A two-piece toilet, characterized in that: The raw materials for preparing the two-piece toilet seat include the sanitary ceramic adhesive slurry according to any one of claims 1-6.
Citation Information
Patent Citations
Repair slurry for sanitary ceramics
CN102942384A
High-hardness wollastonite glaze slip and preparation method thereof
CN104692833A